The Influence of Career Development and Compensation on Turnover Intention with Job Satisfaction as Intervening Variables at PT. MMI (PNM Affiliate) on Madura Island - Muhammad Mirza Doddy Artha; Adi Susilo Jahja (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper investigates the factors that influence turnover intention at PT. MMI (PNM affiliate) on Madura Island. Methods of data collection using questionnaires and interviews. The sampling technique is incidental sampling. The population is 221 employees of PT. MMI on the Madura Island. We analyzed the data with SmartPLS software. The results of the study show that career development and compensation have a positive effect on job satisfaction. Career development has no significant effect on turnover intention. Compensation has a positive effect on turnover intention. Job satisfaction can mediate the effect of career development and compensation on turnover intention